Adipofascial perforator flaps: Its role in reconstruction of soft-tissue defects of lower leg and ankle - Deepak Nanda; Shamendra Anand Sahu; Durga Karki; Sanjay Kumar; Amrita Mandal (Indian Journal of Plastic Surgery)
Background: Despite advances in surgical skills, adipofascial flaps are still less preferred option for coverage of leg defect. We evaluate the use of perforator-based adipofascial flap in small-to-medium-sized soft-tissue defects in the lower limb. Patients and Methods: After localisation of perforators along the major axial vessels in the lower limb using handheld Doppler, adipofascial flap based on the nearest best perforator of anterior tibial artery, posterior tibial artery and peroneal artery was raised to cover soft-tissue defect in 21 patients. The flap was transposed over the defect and covered by split-skin graft. Donor site was primarily closed. Flap complications, functional and aesthetic outcomes are noted in follow-up. Results: There was partial loss of flap in five patients. After debridement and dressings, split-skin grafting was done for four patients and one patient was managed with local flap. Scar over the flap was stable with no reports of recurrent ulceration or breakdown of wound in 6-month follow-up. Four of five patients reported adequate healing of the fractured bone. Average visual analogue score was 8.24/10 for appearance of donor site as evaluated by the patient. Conclusions: Perforator-based adipofascial flap is a good alternative for coverage of small-to-medium-sized soft-tissue defect of the leg, particularly over the malleolus and lower part of the leg. Use of adipofascial tissue and primary closure of the donor site causes minimal donor-site morbidity. Adipofascial perforator flap provides aesthetically superior recipient-site scar with satisfactory functional outcome.